2022
DOI: 10.1002/jez.2638
|View full text |Cite
|
Sign up to set email alerts
|

Impact of photoperiod on uterine redox/inflammatory and metabolic status of golden hamster, Mesocricetus auratus

Abstract: Photoperiod modulates reproductive physiology at multiple levels in seasonally breeding animals. Golden hamsters are long-day breeders that diminish their fertility during the short days. Photoperiod is known to regulate hormonal milieu and uterus is a hormone-sensitive dynamic tissue. However, there is lack of molecular insight regarding the impact of photoperiod on uterine physiology with respect to redox and metabolic status in Mesocricetus auratus. We evaluated the impact of photoperiod onprogesterone [P4]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Hamsters were kept under photoperiodic regime of 12.5 h light/11.5 h dark cycle in which they behave as continuous breeders. [36][37][38] All the experiments conducted for our study were in accordance with the guidelines set by the Committee for the Purpose of Supervision and Control on Experiments on Animals (CPSCEA), Government of India.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hamsters were kept under photoperiodic regime of 12.5 h light/11.5 h dark cycle in which they behave as continuous breeders. [36][37][38] All the experiments conducted for our study were in accordance with the guidelines set by the Committee for the Purpose of Supervision and Control on Experiments on Animals (CPSCEA), Government of India.…”
Section: Animalsmentioning
confidence: 99%
“…The thorough methodology for immunohistochemical detection of PCNA in ovarian sections was carried out using protocol described elsewhere. 19,37 The sections were then examined under Nikon Eclipse E200 research microscope with NIS-Element D software in randomly selected sections.…”
Section: Immunohistochemical Localization Of Proliferating Cell Nucle...mentioning
confidence: 99%
“…Some studies have also demonstrated that FOXO1 plays a key role in autophagy regulation and can upregulate the expression of autophagy-related genes [16]. FOXO signaling plays an important role in a study of photoperiodic effects on uterine metabolism in the golden hamster (Mesocricetus auratus), where photoperiod regulates uterine function-related seasonality through redox/metabolic homeostasis [17]. However, whether FOXO is involved and the role played under photoperiod-induced physiological changes in carp has not been studied.…”
Section: Introductionmentioning
confidence: 99%